Space and Time in a Work of Art - Муродова М. М (Web of Journals Publishing, 2023)
The article deals with the categories of "space", "time" and "chronotope" in a literary text and their main properties.
Keywords: chronotope, localization of space, temporal ontology, oneiric chronotope.